Generating genuine inclusion in higher education utilising an original, transferable, and customisable model for teaching and assessing reflective learning. Issue 4 (4th July 2021) - Taylor, S.; Ryan, M.; Elphinstone, L.
ABSTRACT: The International Covenant on Economic, Social, and Cultural Rights calls for accessible higher education (HE), stating that it is necessary for the full development of the human personality and the sense of its dignity. Education is therefore at the heart of global development goals transforming internationalisation into a core strategic pillar for universities. Amidst pressure on academics to prepare students for real world employment including working in cross-boundary teams, global research trends indicate an indifference to diversity. For post Global Financial Crisis (1987) and Coronavirus Disease (2019) domestic graduates seeking employment in contracting economic markets, indifference intensified to hostility. Addressing these issues using an original customisable model for teaching and assessing reflective learning across HE, a three-stage targeted intervention was prepared and actioned (2008–2020). With research suggesting that high level and complex learning is best developed when assessment, involves students as partners, the intervention included an iterative process of peer review. With 6000 participating Business students, the feedback indicates that scaffolded reflective processes have a powerful effect on students' understanding of assessment tasks and their willingness to work in diverse teams with significant benefits for student outcomes and staff development.